2010
DOI: 10.1155/2010/576151
|View full text |Cite
|
Sign up to set email alerts
|

In situFTIR studies on mammalian cells

Abstract: In this work, we describe the application of FTIR spectroscopy to study lipids and proteins, in cellular systems during heating and cooling. Various spectral analysis methods are described to simultaneously study membrane phase behavior and heat-induced protein denaturation in cells. Membrane phase behavior was studied by following the temperature dependence of the CH2stretching vibration bands. Protein denaturation was studied using the amide-I and -III bands. Both amide-I and amide-III band analysis show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…Absorbance bands arising from endogenous biomolecules are best visible in the dried sample, as water absorbs most of the infrared light causing overlap of bands. Characteristic bands arising from cellular proteins are the amide‐I (1600−1700 cm −1 ), amide‐II (1500−1600 cm −1 ) and amide‐III band (1330−1200 cm −1 ) (Wolkers and Hoekstra ; Wolkers and Oldenhof ). Protein denaturation is evident as changes in the shape of these bands (Wolkers and Oldenhof , ).…”
Section: Use Of In Situ Ftir To Study Biomolecular Structure and Membmentioning
confidence: 99%
See 2 more Smart Citations
“…Absorbance bands arising from endogenous biomolecules are best visible in the dried sample, as water absorbs most of the infrared light causing overlap of bands. Characteristic bands arising from cellular proteins are the amide‐I (1600−1700 cm −1 ), amide‐II (1500−1600 cm −1 ) and amide‐III band (1330−1200 cm −1 ) (Wolkers and Hoekstra ; Wolkers and Oldenhof ). Protein denaturation is evident as changes in the shape of these bands (Wolkers and Oldenhof , ).…”
Section: Use Of In Situ Ftir To Study Biomolecular Structure and Membmentioning
confidence: 99%
“…Characteristic bands arising from cellular proteins are the amide‐I (1600−1700 cm −1 ), amide‐II (1500−1600 cm −1 ) and amide‐III band (1330−1200 cm −1 ) (Wolkers and Hoekstra ; Wolkers and Oldenhof ). Protein denaturation is evident as changes in the shape of these bands (Wolkers and Oldenhof , ). The region below 1500 cm −1 is designated as the finger print region and contains bands that are difficult to assign to specific group vibrations.…”
Section: Use Of In Situ Ftir To Study Biomolecular Structure and Membmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the amide-I band also contains a contribution from the H 2 O scissoring band. In the region below 1500 cm −1 a variety of characteristic molecular group frequencies can be observed that are difficult to assign but the shape of the spectra in this region is characteristic and provides a 'finger print' of the tissue [14].…”
Section: Fourier Transform Infrared Spectroscopic Studies: Assessmentmentioning
confidence: 99%
“…When proteins in tissues are analyzed by FTIR, the amide bands provide information on the overall protein secondary structure of all endogenous proteins [11]. Temperature scanning FTIR studies, in which spectra are acquired while changing the temperature of the sample, can be used to detect heat-induced protein denaturation in cells and tissues [11,14].…”
Section: Introductionmentioning
confidence: 99%